A Lei nº 13.415/2017 no estado do amazonas: projeto de vida ou preparação para o mercado de trabalho?. - Santos, Miriane Feitoza dos (Brasil, 2023)
This work aims to disseminate the main results of the research of the Scientific Initiation Scholarship Program (PIBIC) of the Federal University of Amazonas (UFAM), entitled “The process of implementing the New High School from Law Nº 13.415/2017: actions and perspectives in the context of the State teaching network of Amazonas” carried out between the years 2022 and 2023. In addition to the discussions about the implementation process in the State of Amazonas, the focus of this research was to analyze the transition process to a new curriculum, taking into account consideration the training itineraries offered in schools, and especially discussions on the Life Project discipline, which has been awakening great debates among educators. To answer the research problem, a bibliographical and documentary research was used, using the necessary tools for organizing and systematizing the collected data, such as tables, graphs and schemes built based on the New Middle School Panel prepared by the Ministry of Education (BRASIL, 2018). In the theoretical framework of this study, we will use authors such as Motta and Frigotto (2017), Costa and Coutinho (2018) to discuss Law No. talk about Life Projects. Through the process of data collection, this work will aim to assist in the studies of future researchers who work in the fields of studies on the trajectories of young people in the new high school.